A "shift in attitude"? Institutional change and sexual and gender-based crimes at the Extraordinary Chambers in the Courts of Cambodia. Issue 1 (2nd January 2017) - Palmer, Emma; Williams, Sarah
ABSTRACT: The Extraordinary Chambers in the Courts of Cambodia (ECCC) has been slow to address sexual and gender-based violence (SGBV) crimes perpetrated during the Democratic Kampuchea regime. However, there appears to have been a tentative "shift in attitude" at the ECCC toward the investigation and prosecution of these crimes. This article draws on feminist institutionalist theories, first to explain the ECCC's initial failure to prioritize SGBV and then to explain how and why this may have changed. The article suggests that such change has not arisen from the ECCC's formal rules. Instead, various actors working with and around these "old rules" have drawn on these provisions, civil society initiatives and international and national gender norms to modify "informal" practices concerning the prosecution of SGBV at the ECCC. Sensitivity to SGBV is particularly important in hybrid, or internationalized, international criminal structures, which may be hindered by prohibitive practices emerging from both the international and national components of the institution.